(3eNJUQ CfhGQ Ydh GdCLQGe aj GdcTa Yf CSeGA GdCgQGes - (3GdTQja LeGd GdOjf CHi LYaQ Hf YHO GdYRjR GdEOQjSis; (3CHhGdaJM eMeO Hf SYO Hf eMeO GdOjHGLj GdeQhRj,J (B609 (3g` s
(3ChdgG (B:s
(3hHYO aEfg deG HJGQjN hUhd QSd GdOjhGf GdYRjR s
(3BNQgG (B:s
(3hgPG GdQLd SbQGW dG jbhd gh hGUMGHg Ydi GdPi ajg gPg GdGOdI hGdhMi YfOg gh GdPi jJHY dg hjJUhQ eGdGjchf ZjQg hGdSdGe s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B137s
Keywords: (3GdJGQjNs